Now we wantx ˙= p(t)x + q(t), that is,x ˙− p(t)x = q(t), so we are looking for a function x such that d xe−P (t) = q(t)e−P (t). () dt
Integrating () from t0 to t (using u for our variable of integration), we have t t d −P (u) −P (u) Z x(u)e du = Z q(u)e du. () t0 du t0 Now t t d −P (u) −P (u) Z x(u)e du = x(u)e du t t0 0 () −P (t) −P (t0) = x(t)e − x(t0)e −P (t) = x(t)e − x0 since P (t0) = 0 and x(t0) = x0. Hence we want t −P (t) −P (u) x(t)e − x0 = Z q(u)e du. () t0 1 2 First Order Linear Differential Equations Section
Difference Equations to Differential Equations (50) 来自淘豆网m.daumloan.com转载请标明出处.